Risiko Keuangan Sebagai Determinan Hubungan antara Earning dengan Return pada Bank BUMN - Amilia Paramita Sari (Universitas Batanghari Jambi, 2018)
This research aimed to found whether credit risk could be the earning connection determinant by return within BUMN Banking. The dependent variable of this study is cumulative abnormal return (CAR) whereas independent variable are standardized unexpected earning (SUE), credit risk and interest risk. The sample of this study are BUMN Banking in Indonesia. Data used in this study is secondary one from Annual Report from 2014 to 2017. In order to analized connection between standardized unexpected earning (SUE) to cumulative abnormal return (CAR) and financial risk as connection determinant of both earning by return used double regression analysis. Research result showed that variable of standardized unexpected earning (SUE) have relation to cumulative abnormal return (CAR) and credit risk could be determinant of both earning and return connection.While for interest risk not become determinant of both earning and return connection.